How does democracy influence citizens' perceptions of government corruption? A cross-national study. Issue 5 (28th July 2016) - Li, Hui; Tang, Min; Huhe, Narisong
Abstract : We examine the effect of democracy as an institutional context on individuals' perceptions of government corruption. To do so, we compile an integrated dataset from the Asian, Afro, and Latino Barometer Surveys and use a hierarchical linear regression model. Our primary finding is that the effect of democracy has different effects on ordinary citizens' perceptions of corruption in different contexts. In general, people in countries with higher levels of democracy tend to perceive their governments to be more corrupt. However, more importantly, conditional models show that in countries with more developed democratic institutions, individuals with stronger democratic values are less likely to perceive the government to be corrupt. Moreover, people in such countries are less likely to assess their government based on their perceptions of economic situation.